Construction of Buginese Local Wisdom on the Paradigm of Sharia Banking Development in South Sulawesi - Syaparuddin Syaparuddin (IAIN Ponorogo, 2019)
Abstract: This study aims to assemble Buginese local wisdom into a paradigm in order to develop sharia banking in South Sulawesi. Based on this purpose, the design used is descriptive qualitative design. It means that it describes qualitatively a paradigm built on Buginese local wisdom to develop sharia banking in South Sulawesi. The approach used is cultural and economic approach. While the focus of this study is the economic values of Buginese local wisdom. Therefore, the data used in this study come from Lontara', documents and related books and references. Using literature study in collecting these data and were analyzed with content analysis and inter-text analysis. The result of this study is that the paradigm that can be built on the economic values of Buginese local wisdom, is the humanist paradigm, namely